Application of deep learning models for pest detection and identification - Ayesha Rafique; Madiha Abbasi; Noreen Akram; Quratulain (Mehran University Research Journal of Engineering and Technology)
The quality and productivity of crops are seriously threatened by insect infestations, which is the primary focus of this research. Traditional monitoring methodologies tend to be ineffective and incorrect, resulting in wasted resources and loss of money. By incorporating cutting-edge AI and deep learning technologies, this study unveils a fresh method for rapid and precisely identifying pests in agricultural settings. This research makes use of high-resolution image technologies and Convolutional Neural Networks (CNNs) to showcase the promise of deep learning models in automated pest detection. The generalizability and model performance may be improved using transfer learning techniques leading to more efficient use of available resources. Key goals of this research include extensive testing across varied pest types and environmental settings, combined with the design and refinement of a CNN model specifically engineered for accurate pest identification. The gap between traditional pest monitoring practices and data-driven procedures is filled by the suggested method which ensures a significant increase in agricultural productivity that will contribute to greater food security and overall economic prosperity. This research strengthens the influential effects on agriculture, including enhancement of pest control, increasing food security, and boosting economic expansion. To promote this cutting-edge use of deep learning in agriculture, continuous cooperation between academics, businesses, and farmers is essential.